Hubungan Perilaku Penderita dengan Kejadian Tuberkulosis di Wilayah Kerja Puskesmas Jagir Kecamatan Wonokromo Kota Surabaya - Retno Ardanari Agustin; Florentina Sustini (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2017)
Tuberculosis is a tropical contagious disease that is one of the targets of government programs in the eradication of infectious diseases. Indonesia is now ranked fifth with the highest burden of TB in the world. The results of TB prevalence surveys (2004) on knowledge, attitudes and behavior show that 96% of families care for family members with TB. 85% know that TB can be cured, 26% can name two major signs and symptoms of TB. The mode of transmission of TB is understood by 51% of families. The purpose of this study to determine the relationship of behavior with the incidence of tuberculosis in Puskesmas Jagir Kecamatan Wonokromo Kota Surabaya. The study was conducted November 1, 2014 - January 27 2015, the design of case control research, the risk factor of this study is the behavior of the patient, the effect is the incidence of tuberculosis. Respondents were cases of 10 people and control 26 people. Univariate analysis describes knowledge, attitude, action and behavior respondent. Bivariate analysis using contingency coefficient calculation result. The greater incidence of tuberculosis did not occur in respondents with favorable attitudes (p = 0.013, r = 0.383, OR = 7.667), respondents who carried out preventive measures of transmission (p = 0.001 r = 0.286 OR = 37.5) good (p = 0.001, r = 0.494, OR = 24,429). It is necessary to increase the willingness and behavior (knowledge, attitude and actions) of tuberculosis patients in an effort to reduce the incidence of tuberculosis, by increasing the dissemination of information not only to the patient but also to the community. Keyword: Knowledge, Attitude, Action, Behaviour, Tuberculosis